The influence of baby schema effect and mere exposure effect on implicit and explicit face processing : a follow-up study - Navarini, Nora (2021)
Faces are pivotal social stimuli that convey a tremendous amount of information and trigger numerous cogni-tive processes and consequent behaviors. Among the numerous factors that mediate face perception, we focused our attention on two particular phenomena and their interaction: the Baby Schema effect (BSE) and the Mere Exposure effect (MEE). Accordingly to the BSE, babies’ features are considered “cuter” than adults’ features and motivate people towards protection and caregiving, while the MEE states that familiarity can increase the like-ability of various stimuli, including faces. To investigate how those two factors interact, we carried out a follow-up study of the work of Venturoso et al. (2019) on a Singaporean sample. Singapore is a multicultural city-state where different ethnicities live alongside each other. Participants (ethnic Chinese and Indian) were shown faces of female adults and babies of different ethnic groups (Caucasian, Indian, Chinese and Arabic). Implicit responses were recorded using pupillometry measures, while explicit attitudes were assessed using a questionnaire. Our results confirm the presence of the BSE in both the explicit and implicit measures; specifically, baby faces elicited greater pupillary variations and were rated as more attractive than adult faces. An interaction effect between age and ethnicity was also observed. On the other hand, differences in pupil diameters and pleasantness scores were found between the ethnic groups on adult faces. The above-mentioned differences did not depend on whether stimuli belonged to the ethnic in-group or out-group of the participants, suggesting that exposure to individu-als of different ethnicities reduces in-group favoritism. Further investigation is needed to better understand the complex interaction between BSE and MEE in our increasingly multifaceted reality